Cuproptosis-related LncRNAs are correlated with immunity and predict prognosis in HNSC independent of TMB - Li, Mingyu; Nurzat, Yeltai; Huang, He; Min, Peiru; Zhang, Xiaowen (Frontiers in Genetics, 2023)
Aims: Cuproptosis is a novel cell death pathway, and the regulatory mechanism in head and neck squamous cell carcinoma (HNSC) remains to be explored. We determined whether cuproptosis-related lncRNAs (CRLs) could predict prognosis in HNSC. Methods and Results: First, we identified 10 prognostic CRLs by Pearson correlation and univariate Cox regression analyses. Next, we constructed the CRLs prognostic model based on 5 CRLs screened by the least absolute shrinkage and selection operator (LASSO) Cox analysis. Following this, we calculated the risk score for HNSC patients and divided patients into high- and low-risk groups. In our prognostic model, HNSC patients with higher risk scores had poorer outcomes. Based on several prognostic features, a predictive nomogram was established. Furthermore, we investigated principal component analysis to distinguish two groups, and functional enrichment analysis of 176 differentially expressed genes (DEGs) between risk groups was performed. Finally, we analyzed relationships between tumor mutation burden (TMB) and risk scores. Conclusion: Cuproptosis-related lncRNAs can be applied to predict HNSC prognosis independent of TMB, which is closely correlated with tumor immunity.